The Impact of E-Cornerce on Transport Services - Veselko, Gregor; Jakomin, Igor (Promet - Traffic&Transportation)
The impact of information technologies on transp011 serviceshas been very considerable in the last period. Along thesupply chain there is a variety of different activities going on,from ordering, invoicing, warehousing, shipment, insurance,custom clearance ... A long chain of subjects where each ofthem has an important role.Efficient and effective exchange of infO!mation between allthe involved parties seems to be a great challenge of today. Accomplishingthis will determine the best possible and sustainableposition on the logistics scene.Being successful in this environment today requires big organizationalefforts and financial investment in adequate technology.The basic task of such up-to-date technologies to providefast and reliable information flows between parties involvedin a certain business operation. There is therefore a needfor a good and sound information system.